Predictors of Students’ Intrinsic Motivation in a Biotechnological Out-of-School Student Lab - Röllke, Kerstin; Großmann, Nadine (Frontiers in Education, 2022)
Out-of-school student labs have been established in the field of STEM (science, technology, engineering, and maths) to support students’ motivation regarding science by giving the opportunity for inquiry-based learning in an authentic learning environment. However, previous research most often lacks to explain and investigate determinants of the reported positive effects of such labs on motivation. Therefore, we investigated predictors of students’ intrinsic motivation during a visit to the out-of-school student lab. 170 secondary school students (58% female; Mage = 16.55 years, SDage = 0.58 years) from 12 courses took part in this study. Our results reveal students’ perceived autonomy and competence as predictors of their intrinsic motivation, but not their gender, grade in biology and preparation beforehand. Out-of-school student labs therefore seem to be an important opportunity to foster intrinsic motivation regardless of individual student characteristics. Since our results show a crucial role of students’ perception of autonomy and competence for their intrinsic motivation in the out-of-school lab, opportunities to implement autonomy and competence support are outlined as practical implications.